Race and sex-based disparities associated with carotid endarterectomy in the Atherosclerosis Risk in Communities (ARIC) Study - Hicks, Caitlin W. (Atherosclerosis, 2019)
BACKGROUND AND AIMS: The indications for carotid endarterectomy (CEA) are well established. The aim of the current study was to investigate sex and race-based disparities in the incidence of CEA after adjusting for carotid artery stenosis risk factors. METHODS: We conducted a prospective cohort analysis of 14,492 black and white participants in the Atherosclerosis Risk in Communities (ARIC) study without prevalent stroke at baseline (1987–1989). We used Kaplan-Meier curves and Cox proportional hazards models adjusting for sociodemographic, cardiovascular, and disease severity risk factors to quantify the associations of sex and race with incident CEA. RESULTS: CEA was performed in 330 of 14,492 ARIC participants during a median of 27 years of follow-up [incidence rate 1.00 (95% CI 0.90–1.12) per 1,000 persons-years]. The crude incidence of CEA varied significantly by sex [female vs. male: HR 0.60 (95% CI 0.48–0.74)] and race [black vs. white: HR 0.65 (95% CI 0.49–0.86)]. Adjustment for sociodemographic and cardiovascular risk factors, carotid intima-media thickness, and symptomatic status attenuated the association of sex with CEA [females vs. males HR 0.96 (0.76–1.22)], but black participants had a lower risk of incident CEA after adjustment [HR 0.68 (95% CI 0.49–0.95)]. CONCLUSIONS: We found significant variation in the incidence of CEA procedures based on race that was independent of traditional risk factors and carotid IMT. Whether this disparity is a reflection of differences in disease presentation or access to care deserves investigation.